2019
DOI: 10.1016/j.ymssp.2019.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state regimes prediction of a multi-degree-of-freedom unstable dynamical system coupled to a set of nonlinear energy sinks

Abstract: A general method to predict the steady-state regimes of a multi-degree-of-freedom unstable vibrating system (the primary system) coupled to several nonlinear energy sinks (NESs) is proposed. The method has three main steps. The first step consists in the diagonalization of the primary underline linear system using the so-called biorthogonal transformation. Within the assumption of a primary system with only one unstable mode the dynamics of the diagonalized system is reduced ignoring the stable modes and keepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Set of NESs were recently proposed for passive mitigation of dynamic instability in discrete systems [10,11]. Nonlinear SDOF and MDOF primary systems were considered, respectively, providing the socalled mitigation limit of the NESs, i.e., the value of a chosen bifurcation parameter which separates harmful situations from harmless situations.…”
Section: Introductionmentioning
confidence: 99%
“…Set of NESs were recently proposed for passive mitigation of dynamic instability in discrete systems [10,11]. Nonlinear SDOF and MDOF primary systems were considered, respectively, providing the socalled mitigation limit of the NESs, i.e., the value of a chosen bifurcation parameter which separates harmful situations from harmless situations.…”
Section: Introductionmentioning
confidence: 99%
“…tend to zero). When the coupling term f (q, v,v), which is of the order of magnitude of , is taken into account, the variables q 3 , q * 3 , q 4 and q * 4 do not vanish but their contributions remain minimal and can be neglected [9,22]. Consequently, all the terms related to q 3 , q * 3 , q 4 and q * 4 will be omitted in the following developments.…”
Section: The Reduced Modelmentioning
confidence: 99%
“…A network of parallel NES coupled to a Van der Pol oscillator has been considered in [21]. The prediction of the steady-state regimes of a multi-degree-of-freedom dynamical system having one unstable mode coupled to a set of NES has been performed in [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again the regimes described above have been observed and authors proposed analytical approach which allows to explain and predict some them. The difficulties encountered to differentiate, in the parameters space, mitigated situations from unmitigated situations have been solved in Bergeot and Bellizzi (2019). It has been shown that the transition from mitigated regimes to unmitigated regimes with respect to a parameter variation can involve a discontinuity in the steady-state amplitude profiles.…”
Section: Introductionmentioning
confidence: 99%